Required muscle mass for preventing lifestyle-related diseases in Japanese women - Tanimoto Michiya; Yamamoto Kenta; Gando Yuko; Masani Kei; Kawano Hiroshi; Miyatani Masae; Oh Taewoong; Usui Chiyoko; Sanada Kiyoshi; Higuchi Mitsuru; Tabata Izumi; Miyachi Motohiko (BMC, 2008)
Abstract Background Since it is essential to maintain a high level of cardiorespiratory fitness to prevent life-style related disease, the Ministry of Health, Labour and Welfare of Japan in 2006 proposed to determine the maximal oxygen uptake (Vo2max: mL·kg-1·min-1) reference values to prevent life-style related diseases (LSRD). Since muscle mass is one of the determinant factors of Vo2max, it could be used as the reference parameter for preventing LSRD. The aim of this study was to determine and quantify the muscle mass required to maintain the Vo2max reference values in Japanese women. Methods A total of 403 Japanese women aged 20-69 years were randomly allocated to either a validation or a cross-validation group. In the validation group, a multiple regression equation, which used a set of age and the percentage of muscle mass (%MM, percentage of appendicular lean soft tissue mass to body weight), as independent variables, was derived to estimate the Vo2max. After the equation was cross-validated, data from the two groups were pooled together to establish the final equation. The required %MM for each subject was recalculated by substituting the Vo2max reference values and her age in the final equation. Results The mean value of required %MM was identified as (28.5 ± 0.35%). Thus, the present study proposed the required muscle mass (28.5% per body weight) in Japanese women to maintain the Vo2max reference values determined by the Japanese Ministry of Health Labour and Welfare. Conclusion The estimated required %MM (28.5% per body weight) can be used as one of the reference parameters of fitness level in Japanese women.